Antagonismos de forças na gravura de Adir Botelho : análise estética da série Caldeirão - Pezzin, Paola Sarlo (2015)
This work analyzes the woodcuts Calderão series (1986-1996) from the teacher Adir Botelho (1932- ). As this is a work in which war, politics and religion mix their symbolic loads invite us to travel for long and different paths traced by the artist and go